Grasping and appropriating epistemic relevance in the Humanities and Social Sciences: a critical realist argument - Letsekha, Tebello (My University, 2022)
The end of 2017 marked a significant change in South African higher education. The government announced that free higher education would be extended to poor and working class students. For students who had been engaged in protest action demanding free, decolonial, Afrocentric, intersectional and socialist education, this was a partial victory. While concessions were made regarding fees and the removal of statues from the colonial era, South African students continue to grapple with the epistemically alienating nature of disciplinary knowledge in higher education. This struggle is not unique to the students who were part of the 2015-2016 student movements. South African students have legitimately challenged the epistemic dimensions of inequality and exclusion in education since the early 1960s, when Black student movements demanded cognitive justice, rejecting colonial and apartheid ideas at an intellectual level. While it is likely that the powerful disciplinary knowledge offered throughout higher education results in epistemic inequality and exclusion, the arguments presented here are limited to the humanities and social sciences. I have received my disciplinary training in these fields, which change continuously by virtue of their being elements of a culture always in a condition of transition, thus transforming through internal dispute, contestation, revision of methods, politics and philosophies. Although this transformation process is often slow and fraught with challenges, in the South African context these fields continue to reflect white, European male culture and epistemology. Adopting these representations of reality outside of the contexts which have given rise to them results in the distortion of certain ways of knowing, thinking and of seeing one’s own context. Here I propose the adoption of epistemic relevance as a curricular and pedagogical principle to guide the process of grounding disciplinary knowledge in “other” contexts, thus ensuring epistemic and cognitive justice. In sociology, we utilise the notion of “otherness” to analyse the construction of minority and majority identities. The concept is central to the way in which identity categories are established as dichotomies. The notion “otherness” is utilised in this study to highlight the inherently unequal relationship between scholarly communities in the global North and South, which has an impact on whose knowledge is included and excluded in university classrooms. It is also useful in highlighting forms of inequality amongst knowers. It is important to highlight these dichotomies of otherness in relation to epistemic forms of inequality and exclusion as they have been set up as being natural. Dichotomies of otherness in relation to representations of reality are not natural – they represent rather an established social order and hierarchy which has resulted in the hegemony of perspectives from certain contexts and the silencing of others. This needs to change, and it can. The argument advanced in thesis is underpinned by critical realist philosophy, and suggests that if we separate the nature of an underlying reality from knowledge of that reality, thus avoiding the epistemic fallacy, grounding disciplinary knowledge in the local context is possible. The separation of ontology and epistemology is necessary because they operate in two different dimensions – the latter transitive and changing, the former intransitive and relatively enduring. Being epistemically relevant requires that we acknowledge that our knowledge about reality is a result of social conditioning and, thus, cannot be understood independently of the social actors involved in the knowledge-creation process. The adoption of epistemic relevance requires that we ask questions about the context, identity and culture of the knower and producer of the disciplinary knowledge disseminated in the university. Adopting epistemic relevance as a curricular and pedagogical principle makes it possible to move towards epistemic pluralism, thus transcending the dominance of Western epistemologies.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, 2022